Normal Ranges of Left Ventricular Strain: A Meta-Analysis - Yingchoncharoen, Teerapat; Agarwal, Shikhar; Popović, Zoran B.; Marwick, Thomas H. (Journal of the American Society of Echocardiography, 2013)
The definition of normal values of left ventricular global longitudinal strain (GLS), global circumferential strain, and global radial strain is of critical importance to the clinical application of this modality. The investigators performed a meta-analysis of normal ranges and sought to identify factors that contribute to reported variations. MEDLINE, Embase, and the Cochrane Library database were searched through August 2011 using the key terms “strain,” “speckle tracking,” “left ventricle,” and “echocardiography” and related phrases. Studies were included if the articles reported left ventricular strain using two-dimensional speckle-tracking echocardiography in healthy normal subjects, either in the control group or as a primary objective of the study. Data were combined using a random-effects model, and effects of demographic, hemodynamic, and equipment variables were sought in a meta-regression. The search identified 2,597 subjects from 24 studies. Reported normal values of GLS varied from −15.9% to −22.1% (mean, −19.7%; 95% CI, −20.4% to −18.9%). Normal global circumferential strain varied from −20.9% to −27.8% (mean, −23.3%; 95% CI, −24.6% to −22.1%). Global radial strain ranged from 35.1% to 59.0% (mean, 47.3%; 95% CI, 43.6% to 51.0%). There was significant between-study heterogeneity and inconsistency. The source of variation was sought between studies using meta-regression. Blood pressure, but not age, gender, frame rate, or equipment, was associated with variation in normal GLS values. The narrowest confidence intervals from this meta-analysis were for GLS and global circumferential strain, but individual studies have shown a broad range of strain in apparently normal subjects. Variations between different normal ranges seem to be associated with differences in systolic blood pressure, emphasizing that this should be considered in the interpretation of strain.